Insiders, Outsiders and Performance of Vietnamese Firms - Richard Beason; Tu Thi Thanh Tran; Dong Phuong Dao; Hong Minh Nguyen (Gadjah Mada International Journal of Business, 2022)
The consensus in the finance literature is that a large proportion of inside ownership (defined as greater than 5% share ownership by non-institutional holders, managerial holdings, founding family holdings, cross-shareholdings by affiliated firms and ownership by creditors) tends to be associated with more unsatisfactory performance (as measured by ROE or ROA) when compared to firms with lower inside ownership, all else equal. However, this need not be the case if insiders act as monitors of the firm and have the same interest in returns as outsiders.  Ownership structure and firm level financial performance have not been widely studied in Vietnam.  Using data from 729 listed firms in Vietnam for 2018, we test the hypothesis that greater insider ownership has a negative impact on firm performance. We found that Vietnam's insiders play a monitoring role, exercising their relative power to ensure the firm's profitable functioning. These findings are inconsistent with research on Japanese groupings, as well as other findings. The Vietnamese stock market does not appear to be negatively affected by insider influence; indeed, insiders appear to act as positive monitors.